NSCA's guide to high school strength and conditioning - McHenry, Patrick; Nitka, Mike
"This book is a resource for strength and conditioning professionals and administrations in the high school environment. There will be a variety of components found in the book such as exercise descriptions, class lesson plans, curricula programming, coach and teacher checklists, and facility design and layout diagrams"--Provided by publisher.